PRINCIPLES OF CONSTRUCTION OF THE GENERALIZED MATHEMATICAL MODEL OF THE HYDRAULIC EXTINGUISHER OF OSCILLATIONS OF THE PASSENGER CAR (Transport systems and technologies, 2021)
The study of the processes associated with the use of working fluids in the elements of hydraulic drives was preceded by studies of the unsteady periodic movement of the working fluid in the pipelines of hydraulic systems. Such processes take place in hydraulic drives and their elements, and are associated with the compressibility of the working fluid. The stability of the operation of hydraulic valves, which are supplied to hydraulic systems in order to maintain, within the required limits, pressures or flow rates, is also largely predetermined by non-stationary hydro mechanical processes occurring in the pipelines of these systems, channels and chambers of hydraulic devices. The peculiarities of the working processes of passive vibration dampers of passenger cars include the interaction of the working fluid with moving parts and its flow through the channels and through the calibrated holes with local artificial resistance. For in-depth analysis of changes in operating parameters, it is necessary to use a mathematical model that should reflect the processes that occur during the operation of the hydraulic device. In the presented article the generalized mathematical model of the hydraulic damper of fluctuations of the passenger car of the НЦ-1100 type is developed. This model takes into account the special operating conditions of the hydraulic shock absorber, which allows you to study the impact of operating parameters on the performance of the device.
Keywords: hydraulic vibration damper, mathematical model, hydro mechanical processes, parameters of the working fluid.